Ensemble methods in data mining improving accuracy through combining predictions - Seni, Giovanni; Elder, John F. 1961- (Morgan & Claypool Publishers, 2010)
1. Ensembles discovered -- Building ensembles -- Regularization -- Real-world examples: credit scoring + the Netflix challenge -- Organization of this book --
Keywords: Data mining; Electronic books